Postoperative chemotherapy in patients with rectal cancer receiving preoperative radio(chemo)therapy: A meta-analysis of randomized trials comparing surgery ± a fluoropyrimidine and surgery + a fluoropyrimidine ± oxaliplatin. Issue 6 (June 2015) - Bujko, K.; Glimelius, B.; Valentini, V.; Michalski, W.; Spalek, M.
Abstract Background There is no consensus on the role of postoperative chemotherapy in patients with rectal cancer who have received preoperative radio(chemo)therapy. Materials and methods A systematic review and meta-analysis were performed of trials that used preoperative radio(chemo)therapy and randomized patients either between postoperative chemotherapy and observation or between a fluoropyrimidine only (FU-only) and a fluoropyrimidine with oxaliplatin (FU–OXA) as postoperative chemotherapy. Results Five randomized studies compared postoperative chemotherapy with observation in a total of 2398 patients. None of these trials demonstrated a statistically significant benefit of chemotherapy for OS and DFS. The pooled differences in OS and DFS did not differ statistically significantly between the chemotherapy group and the observation group. The hazard ratios (HRs) and 95% confidence intervals (CIs) were 0.95 (CI: 0.82–1.10), P = 0.49 and 0.92 (CI: 0.80–1.04), P = 0.19, respectively. In the subgroup of trials in which randomization was performed after surgery (n = 753), a statistically significant positive pooled chemotherapy effect was observed for DFS (HR = 0.79, 95% CI: 0.62–1.00, P = 0.047), but not for OS (P = 0.39). Four randomized trials compared adjuvant FU–OXA with adjuvant FU-only in 2710 patients. In two trials, the difference in DFS between groups was statistically significant in favour of FU–OXA, and in the other two trials, the difference was not significant. The pooled difference in DFS between the FU–OXA group and the FU-only group was not statistically significant: HR = 0.84 (CI: 0.66–1.06), P = 0.15. Conclusion The use of postoperative chemotherapy in patients with rectal cancer receiving preoperative radio(chemo)therapy is not based on strong scientific evidence.